Influences of knowledge, information technology and logistics management on financial performance in Malaysia’s manufacturing companies - Cheng, Si Pei (2020)
Malaysia’s shift from a commodity and agricultural-based low-yield economy into a middle-high-yield economy was due to its sustained rapid economic growth. Although the manufacturing sector is stated as the second largest benefactor to Gross Domestic Product (GDP) after the services industry, it faces weak external demand and stiff competition from emerging economies after the global financial turmoil. But the organisation can build up their supply chain activities through advanced knowledge management, integration of information systems into supply chain and well-structured logistics management to overcome the crisis, create value for customers and increase the company’s competitive strength in market. Employees possesses with supply chain-related knowledge, associated with advanced information technology and improved logistic services will boost customer service, decreasing operating cost and ameliorating company’s financial position. The study examines the relationship of the knowledge management, information technology and logistics management on the financial performance of the listed manufacturing companies in Malaysia quantitatively through a cross-sectional study. This study utilised a sample of 311 listed companies in manufacturing sector from the financial data which obtained through Osiris Database from the research period of the year 2008 to the year 2012. The independent variables for supply chain management practices such as knowledge management, information technology and logistics management which are measured by proxies such as total assets (TA), total sales (TS), and return on capital employed (ROCE); whereas the dependent variables for companies’ financial performance is measured by proxy such as return on assets (ROA). Research framework is designed and hypotheses are constructed to identify the relationship between the supply chain management practices and companies’ financial performance. Descriptive statistics, correlation test, multicollinearity, multiple regression test, and hypothesis test are conducted. The findings of this research show that logistics management which is measured by proxy like ROCE has significant effect on company’s financial performance in the term of ROA. On the other hand, knowledge management and information technology which are measured by proxies such as total assets (TA) and total sales (TS) have no significant effect on the company’s financial performance in the term of ROA. This research summarised that it can provides useful information for different users who can generate benefit from the financial information and assist in decision making by understanding the factors that influences supply chain management which will enable organisation to maintain its competitive advantage and sustain in this high-end technology era. Finally, the researcher recommends the government or organisations should implement a guideline that provides comprehensive financial information for various entities on judging the financial standing and financial health of the company.